Leadership competency portfolio for universities: A behavioural event- interview approach - Jais, Ismie Roha Mohamed; Azman, Azian Mohmad; Abidin, Ahmad Shakirin Zainal; Ghani, Erlane K (International Journal of Innovative Research and Scientific Studies, 2023)
Leadership has long been disputed due to its importance in organizations particularly in higher education institutions. The Malaysian ministry of higher education established Akademi Kepimpinan Pendidikan Tinggi (AKEPT) which is involved in leadership talent management for the country's higher education institutions. This paper presents the development of an AKEPT leadership competency portfolio for universities using the Behavioural Event Interview (BEI) instrument. It used the qualitative group method through a focus group discussion. The findings showed that the BEI instrument can be used to determine the competency level of academics in universities. There are five levels of leadership competency: level 1 as an individual contributor, level 2 as daily task supervision, level 3 as managing a function, level 4 as integrating diverse functions and level 5 as leading the whole organization. This study found that the committee developed five competency variances comprising significantly exceeds, exceeds, suitable, developable and reviewable. This paper provides insight into how higher education institutions in Malaysia sustain an organizational culture of excellence. In addition, it provides a model for other educational institutions in developing a leadership competency portfolio.